Transcutaneous Acupoint Electrical Stimulation on Chemotherapy-Induced Constipation for Non-Small Cell Lung Cancer Patients: A Randomized Controlled Trial - Ting Mao; Xiangyu Liu; Qinqin Cheng; Yongyi Chen (Elsevier, 2021)
Objective: Chemotherapy-induced constipation (CIC) adversely affects the quality of life of non-small cell lung cancer (NSCLC) patients. This study aimed to investigate the clinical effects of transcutaneous acupoint electrical stimulation (TAES) on CIC. Methods: Sixty NSCLC patients who received chemotherapy at Hunan Cancer Hospital, Changsha, China, were assigned to the TAES (n = 30) or control (n = 30) group using Research Randomizer. In the TAES group, four acupoints, namely Tianshu, Quchi, Zusanli, and Shangjuxu, were stimulated six times a week, lasting for 4 weeks, while the control group received the usual care. The Bristol Stool Form Scale (BSFS) and the Constipation Assessment Scale (CAS) were used. Results: Both the BSFS and CAS scores for the experimental group were significantly higher than that for the control group (P = 0.004 and P < 0.001 separately). Conclusions: TAES was effective for alleviating constipation in NSCLC patients receiving chemotherapy and was a safe and practical nursing intervention.